Discovery of 1, 3‐Diaryl‐pyridones as Potent VEGFR‐2 Inhibitors: Design, Synthesis, and Biological Evaluation. (11th January 2016) - Yan, Wei; Huang, Zhaoru; Wang, Zhengyu; Cao, Sufen; Tong, Linjiang; Zhang, Tao; Wang, Chen; Zhou, Lin; Ding, Jian; Luo, Cheng; Zhou, Jinpei; Xie, Hua; et al.
Abstract : In this study, we described the design, synthesis, and biological evaluation of 1, 3‐diaryl‐pyridones as vascular endothelial growth factor receptor‐2 (VEGFR‐2) inhibitors. The 1, 3‐diaryl‐pyridones were synthesized via Chan‐Lam and Suzuki coupling reactions. Two representative compounds, 17 and35h, displayed excellent enzymatic inhibitory activities, with IC50 values of 3.5 and 3.0 nm, respectively. Furthermore, compounds17 and35h blocked the tube formation and suppressed the VEGF‐induced phosphorylation of VEGFR‐2 and downstream extracellular signal‐regulated kinases (Erk) in human umbilical vein endothelial cells (HUVECs) at 10 nm concentration. The docking simulation showed that compound17 bound well into the active site of VEGFR‐2 via two hydrogen bonds and hydrophobic interactions. Abstract : Synthesis and biological evaluation of a novel series of 1, 3‐diaryl‐pyridone derivatives as VEGFR‐2 inhibitors were described. Two representative compounds, 17 and35h, exhibited excellent in vitro antiangiogenic activities. Docking simulation showed that compound17 bound well into the active site of VEGFR‐2 with two hydrogen bonds and hydrophobic interactions.